Cognitive impairment, neuroimaging abnormalities, and their correlations in myotonic dystrophy: a comprehensive review - Wu, Yanyun; Wei, Qianqian; Lin, Junyu; Shang, Huifang; Ou, Ruwei (Frontiers in Cellular Neuroscience, 2024)
Myotonic dystrophy (DM) encompasses a spectrum of neuromuscular diseases characterized by myotonia, muscle weakness, and wasting. Recent research has led to the recognition of DM as a neurological disorder. Cognitive impairment is a central nervous system condition that has been observed in various forms of DM. Neuroimaging studies have increasingly linked DM to alterations in white matter (WM) integrity and highlighted the relationship between cognitive impairment and abnormalities in WM structure. This review aims to summarize investigations into cognitive impairment and brain abnormalities in individuals with DM and to elucidate the correlation between these factors and the potential underlying mechanisms contributing to these abnormalities.